2017
DOI: 10.1111/cdev.12897
|View full text |Cite
|
Sign up to set email alerts
|

Playing With Ideas: Evaluating the Impact of the Ultimate Block Party, a Collective Experiential Intervention to Enrich Perceptions of Play

Abstract: Parental attitudes shape play opportunities afforded to children in home, community, and school settings. This study presents evaluation of an intervention designed to enrich parent's conception of play and its relationship with socially valued skills and capacities. On the basis of data from 291 racially and ethnically diverse parents/caregivers of young children (median age between 3 and 6) attending an event in NYC, we find the intervention helped parents conceptualize play in complex ways and altered perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The Ultimate Block Party (UBP) [52,65] served as the first pilot test for Learning Landscapes. UBP sought to transform caregiver attitudes about the relationship between play and learning in a community setting.…”
Section: Ultimate Block Party: Is It Possible To Bring People Togethementioning
confidence: 99%
See 2 more Smart Citations
“…The Ultimate Block Party (UBP) [52,65] served as the first pilot test for Learning Landscapes. UBP sought to transform caregiver attitudes about the relationship between play and learning in a community setting.…”
Section: Ultimate Block Party: Is It Possible To Bring People Togethementioning
confidence: 99%
“…The goal of the evaluation was three-fold: (1) to measure the UBP event's success in conveying 4 core messages about play to caregivers; (2) to determine how well the UBP event's organization supported achievement of its goals; and (3) to learn about people's general attitudes with respect to play in order to inform future strategy for the UBP initiative and other forms of play advocacy. With regard to the measurement of caregiver attitudes, the researchers designed a short survey featuring Likert scale items, open-ended questions, and demographic questions to assess caregiver attitudes and beliefs about play and learning [52]. Results suggested that caregivers' ability to represent different facets of the play/learning connection is a vital component in public awareness and may have been strengthened through direct exposure to multiple forms of play [52].…”
Section: Ultimate Block Party: Is It Possible To Bring People Togethementioning
confidence: 99%
See 1 more Smart Citation
“…The first involves the intervention's resiliency in the face of turbulent real‐world conditions, including high turnover among staff (Farran et al., ), transitory relationships with participants (Dubois et al., ), and changing circumstances in the settings in which the expansion is taking place (Reynolds et al., ). The second emerges from inevitable heterogeneity: variation in children's needs (Roben et al., ); parent, teacher, and community expectations (Weber et al., ; Grob et al., ); resource availability (Reynolds et al., ; Farran et al., ); and the prevalence and form of external constraints on implementation (Schindler et al., ).…”
Section: Persisting Challenges For the Fieldmentioning
confidence: 99%
“…Every intervention designed to enhance child development embodies elements of multiple principles, strategies, and theories of change (Galinksy et al., ; Farran et al., ). When taken out into the world, however, participants are often exposed to only a portion of the elements that were possible (Dubois et al., ; Grob et al., ) and sometimes particular aspects of the program are foreclosed or altered (Reynolds et al., ; Farran et al., ). As a number of the articles illustrate, these considerations require careful and creative measures of “exposure” to the program—conventional notions of dose–response that measure only participants’ time in the program are often too limited to appropriately assess a program's impact, because that impact depends in large part on how they encounter the intervention.…”
Section: Persisting Challenges For the Fieldmentioning
confidence: 99%